2001
DOI: 10.1111/1467-8683.00248
|View full text |Cite
|
Sign up to set email alerts
|

Women Directors on Top UK Boards

Abstract: Research suggests that more diversity in board membership could improve overall performance. This paper considers the business case for increased numbers of female directors, and the lack of female representation on UK FTSE 100 company boards in 1999 and 2000. It also offers a comparison to US data. In 1999, almost two‐thirds of FTSE 100 companies had at least one female director, but numbers had dropped by July 2000 from 64 per cent to 58 per cent, paralleling the levelling‐off at top level reported in North … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
133
2
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 165 publications
(157 citation statements)
references
References 23 publications
8
133
2
2
Order By: Relevance
“…Gender diversity has developed to be one of the challenging research issues as the numbers of women in top management as well as on corporate board increases (Singh, Vinnicombe, & Johnson, 2001). Gender diversity may benefit the board's decision making process.…”
Section: Director's Gendermentioning
confidence: 99%
“…Gender diversity has developed to be one of the challenging research issues as the numbers of women in top management as well as on corporate board increases (Singh, Vinnicombe, & Johnson, 2001). Gender diversity may benefit the board's decision making process.…”
Section: Director's Gendermentioning
confidence: 99%
“…The relationship between the number of women directors and company size (measured usually by market capitalization) has been reported by Catalyst (2003) in the US and Singh, Vinnicombe and Johnson (2001) in the UK. Hyland and Marcellino (2002) also found that larger organizations measured by revenues employ more women directors.…”
Section: Previous Gender Composition Findings and This Studymentioning
confidence: 85%
“…This leads to the following hypothesis: H1: The proportion, existence and/or number of women directors on a property trust s board is greater in larger (measured by market capitalization) entities. Singh, Vinnicombe and Johnson (2001) report that women directors in the UK are particularly found in retailing and banking (where a high percentage of the workforce are women) and also in health, media/publishing and utilities. The office property trust sector and the retail property trust sector had 17 and 11 IPO listings respectively over the period of the study.…”
Section: Previous Gender Composition Findings and This Studymentioning
confidence: 99%
See 2 more Smart Citations